2020
DOI: 10.1021/acs.chemmater.0c02926
|View full text |Cite
|
Sign up to set email alerts
|

Alloying with Sn Suppresses Sintering of Size-Selected Subnano Pt Clusters on SiO2 with and without Adsorbates

Abstract: Using Pt in the form of sub-nanometer dispersed clusters is a way to save precious metal in catalysis, but making such clusters stable against sintering is an uphill battle. Sn is a known agent used to increase the selectivity of dehydrogenation of alkanes on Pt. Through a joint experimental and theoretical approach, we show that adding Sn to the size-selected Pt clusters deposited on amorphous SiO 2 also dramatically enhances the thermal stability of the clusters against sintering.CO temperature programmed de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 66 publications
7
47
0
Order By: Relevance
“…Most DFT calculations were performed on fairly flat substrates, while in reality the silica surface is far less uniform and could restrict the larger amplitude motions of the complex. 100 This is in agreement with prior work that has shown that the dynamics of silane functionalities are affected by the synthetic approach used to make the silica. 43 We have also attempted to release the complex and enable its free rotation by wetting it with benzene or 1,1,2,2tetrachloroethane, and also by dehydroxylating the surface at a higher temperature of 700 °C.…”
Section: Dynamicssupporting
confidence: 90%
“…Most DFT calculations were performed on fairly flat substrates, while in reality the silica surface is far less uniform and could restrict the larger amplitude motions of the complex. 100 This is in agreement with prior work that has shown that the dynamics of silane functionalities are affected by the synthetic approach used to make the silica. 43 We have also attempted to release the complex and enable its free rotation by wetting it with benzene or 1,1,2,2tetrachloroethane, and also by dehydroxylating the surface at a higher temperature of 700 °C.…”
Section: Dynamicssupporting
confidence: 90%
“…The agglomeration of Ru on SiO 2 was not surprising and is most likely due to the weak cluster-surface interaction between Ru and SiO 2 ; previous studies have also shown agglomeration of small clusters on SiO 2 at temperatures below 800 K. 63,73 In addition to aggregation of the Ru clusters, there is also most likely a change in either the cluster structure (beyond agglomeration) or cluster-surface interaction with repeated CO-TPD cycles; this is evidenced by the peak CO desorption temperature decreasing with each CO-TPD cycle, meaning CO is adsorbing less strongly to the clusters aer agglomeration. This is also supported by earlier studies by Anderson and coworkers, 59,71,72 who have shown that for both Pt n /alumina (2 # n # 18) and Pt n /silica (n ¼ 4, 7, 12, 24), the intensity of the high temperature CO-TPD peak increased as cluster size increased, but that repeated CO-TPD cycles caused the peak decrease in intensity and shi to lower temperatures. This provided evidence in the case of small Pt clusters that agglomeration produces different structures than those produced by deposition of larger size-selected clusters.…”
Section: Cluster Agglomeration For Ru 3 /Siosupporting
confidence: 87%
“…A differentiating effect is an intra‐cluster charge separation, which is found only in Pt 3 , Pt 7 , and also in Pt 8 (Supporting Information, Table S1). Such a separation was previously proposed to be the cause of the experimentally seen sintering resistance of Pt 4 Sn 3 /SiO 2 , [55] as it hindered cluster dissociation and monomer migration on the ionic support during Ostwald ripening. For Pt n /TiO 2 , a possible reason for the magic number stability of Pt 3 and Pt 7 can therefore be proposed: A homolytic dissociation creating a neutral Pt atom on the support requires an electronic structure reorganization within the cluster, likely associated with a concurrent shape change, and thus, being energetically costly.…”
Section: Resultsmentioning
confidence: 88%